A New Method to Predict Shock-Type Coal-Gas Outburst Disaster and Its Application. (30th January 2023) - Lyu, Pengfei; Li, Tan; Chen, Xuehua
Abstract : Coal-gas outburst is the one of most serious coal mine dynamic disasters which affects safety mining, with 39 deaths reported during 2019 in China. The mechanism of coal-gas outbursts is complex, and the prediction methods are immature at present. This article was based on previous research results. Firstly, the occurrence mechanism of coal-gas outburst disasters was summarized. It is clear that the occurrence of coal-gas outburst disasters is jointly affected based on the stability of the static structure of coal-rock, the gas parameters, and the release intensity of shock stress. Secondly, the stability evaluation models of coal-rock static structure, gas parameters, and shock stress release intensity were built, respectively, based on the influence factors. Then they were coupled and supposed to form a new prediction model. Finally, the prediction method was applied to the Ji15 -17200 working face of No.12 coal mine in Pingmei company. The working face was divided into three danger levels including weak outburst danger area, medium outburst danger area, and strong outburst danger area. The accuracy of the predicted results was analyzed based on the actual mining condition of the Ji15 -17200 working face. The results show that prediction accuracy is high, and it can be used for actual applications. The research results are of guiding significance to better prevent and control coal-gas outburst accidents and ensure safe production in coal mines.